CUSTOMER SATISFACTION OF CIGARETTE PRODUCTS RELATED TO PRODUCT QUALITY AND PRICE - Ambo Sakka Hadmar; Andi Asnur Pranata M. H (Jurnal Multidisiplin Sahombu, 2022)
This research aims to identify the impact of product quality and price on consumer happiness for Camel Mild Option Purple Cigarettes by PT Japan Tobbaco International in Bandung. This research is a quantitative research with 56 respondents. To ensure sample information using a questionnaire on a google form by scattering it online. Information obtained using SPSS 26 using the multiple linear regression analysis method. Information analysis using multiple linear regression, correlation experiments, verification experiments, partial experimental analysis with t experiments and f experiments (simultaneously) proves that product quality affects purchase decisions, price affects purchase decisions, on the other hand product quality and price in a similar way affect to purchase decisions.